Isu Global dan Transformasi Pembelajaran Ilmu Pengetahuan Sosial (IPS) di Era Modern - Ragil Pangestu; Ranti Sabariani; Ronadia Ronadia; Sani Safitri (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
The Social studies has an important role in education, namely understanding the wider social world so that students are able to face the challenges of global issues. This research explores the transformation of social studies learning in the modern era, focusing on contemporary global issues such as climate change, geopolitical conflicts, economic disparities, health problems, and human rights violations. Through a qualitative-descriptive approach and literature study, this research examines the urgency of social studies education transformation in responding to these issues. The results show that social studies education needs to adopt more interactive and technology-based learning methods, integrate character values, improve digital literacy, and incorporate global issues into the curriculum, the key role of teachers as facilitators and continuous evaluation to ensure the effectiveness of the transformation. This study concludes that a comprehensive transformation of social studies learning is essential to prepare the younger generation to be responsible global citizens and able to contribute to a better society.